Are Dayak Moslem Women Dependant?: A Study of Dayak Moslem Women Work Ethics - Ajahari; Mualimin; Aris Sugianto (MUWAZAH : jurnal kajian gender, 2022)
This study challenges the dominant assumption that women in traditional societies are economically dependent, unproductive, and confined to domestic roles. Focusing on the Dayak Moslem women in Tangkahen village, Central Kalimantan, Indonesia, this research aims to reveal a contrasting reality that defies such generalizations. Situated within the broader discourse on gender, labor, and work ethics, the study explores how socio-cultural and religious values influence women’s roles in sustaining family economies. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, prolonged observations, and documentary studies. Findings indicate that the women of Tangkahen perform dual roles—managing household duties while actively participating in income-generating activities such as farming, trading, and rubber tapping—without compromising their domestic responsibilities. These roles are deeply rooted in cultural, spiritual, and economic motivations      and are perceived not as burdens but as expressions of agency and social identity. The study concludes that women's work ethics in traditional societies are contingent upon embedded social norms, religious beliefs, and local gender constructs. Thus, the generalized negative perceptions about women's work ethics in traditional communities are not universally valid and must be reassessed through culturally grounded and context-sensitive inquiry.